Does self-perceptions and income inequality match? The case of subjective social status - Philipp Poppitz (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2016)
This paper examines subjective social status to test whether individual comparisons are driven by income and wealth, or social and cultural capital as defined by Bourdieu. The empirical analysis uses a cross-sectional data set of 18 European countries and a mixed model with an MCMC estimation method. The results show that material factors are just as important as non-material factors. Besides income and wealth, other dimensions of inequality including education, occupational prestige, parental background and working status are important factors to explain the gap between the income distribution and subjective social status. The most relevant institutions to explain the cross-country differences within Europe are the GDP level, average health and the education system, which also moderates the relevance of wealth on subjective social status. – – Die Arbeit untersucht die Wahrnehmung von Ungleichheit am Beispiel des subjektiven sozialen Status für 18 europäische Länder. Die empirische Untersuchung auf Basis des ISSP 2009 nutzt ein "mixed-effects" Modell welches mittels MCMC geschätzt wird. Der subjektive soziale Status hängt dem Modell zufolge nicht nur von Einkommen und Vermögen ab, sondern auch maßgeblich von anderen Dimensionen sozialer Ungleichheit wie Bildung, Prestige des Berufs, Status des Elternhaushaltes und Beschäftigungsstatus. Diese Faktoren erklären damit einen Teil der Differenz zwischen Einkommensungleichheit und wahrgenommener Ungleichheit. Die Unterschiede im subjektiven sozialen Status zwischen den europäischen Ländern hängen vor allem mit dem BIP, der durchschnittlichen Gesundheit und der Qualität des Bildungssystems zusammen.
urn:nbn:de:101:1-201607296628
Keywords: D31; C21; I24; Z13; 330; Inequality; Perception; Social Status; Bourdieu; Education